2018
DOI: 10.31768/2312-8852.2018.40(1):82-84
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal Yolk Sac Tumor Infiltrating the Heart

Abstract: Background: As a rare tumor, yolk sac tumor is a type of neoplasm that appears like the yolk sac, extraembryonic mesenchyme, and allantois. The mediastinum is the second most frequent area after the gonadal area. Case report: We present an extremely rare case of 15 years old boy with mediastinal yolk sac tumor. The boy came with the chief complaint of swelling of the neck and face. Computed tomography scan of the chest revealed bulky mass with a cystic component that infiltrated the heart. The diagnosis of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…12,18,24 In this literature review, only one patient (1.9%) received radiation therapy alone. 12 It is difficult to assess the efficacy of radiotherapy. But the prognosis of this patients was discouraging.…”
Section: Referencementioning
confidence: 87%
See 2 more Smart Citations
“…12,18,24 In this literature review, only one patient (1.9%) received radiation therapy alone. 12 It is difficult to assess the efficacy of radiotherapy. But the prognosis of this patients was discouraging.…”
Section: Referencementioning
confidence: 87%
“…He is 15‐year‐old male patient of PMYST with superior vena cava syndrome. No evidence of tumor atrophy was found, and the patient died soon after radiotherapy, lost the chance for further chemotherapy or surgery 12 . Bilgehan et al reported that combined treatment of radiotherapy together with surgery and chemotherapy provided more than 284 months survival for a 2‐year‐old female patient 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mediastinum is the second most frequent area after the gonadal area. 1,2 Primary mediastinal yolk sac tumor is rare and carries a grave prognosis. Most patients are young and male.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor is usually located in the gonadal site, and may occur along the midline route of the reproductive crest as the germ cells migrate from the yolk sac. The mediastinum is the second most frequent area after the gonadal area 1,2 . Primary mediastinal yolk sac tumor is rare and carries a grave prognosis.…”
Section: Introductionmentioning
confidence: 99%